Computerized planimetry to assess clinical responsiveness in a phase II randomized trial of topical R333 for discoid lupus erythematosus. (12th June 2018) - Presto, J.K.; Okon, L.G.; Feng, R.; Wallace, D.J.; Furie, R.; Fiorentino, D.; Werth, V.P.
Summary: Discoid lupus erythematosus (DLE) is a skin condition that causes red scaly lesions which often leave behind dyspigmentation (discolouration) and scars. It is an autoimmune disease, which means that the body's immune system attacks normal skin. Sunlight has also been shown to play a role in this disease with most patches, called lesions, occurring in body areas exposed to ultraviolet radiation. DLE involves the skin, with or without the type of lupus called systemic lupus erythematosus (SLE). About 15 to 30 percent of SLE patients will develop DLE. Janus Kinase, or JAK, are a group of enzymes in the body involved in the development of the disease. Researchers have been working to find medicines that will inhibit JAK as it is thought that doing so will improve patients' symptoms. This study, from the United States and Canada, assessed the effectiveness of a therapy called R333. R333 is a 'topical' ointment, meaning a medicine applied directly to the skin, that works by blocking the signaling of JAK and spleen tyrosine kinase (Syk), which is also involved in the disease. In the trial, we compared R333 to a placebo ointment. The results showed that four weeks of R333 treatment did not result in significant clinical improvement. However, further studies with different formulations are necessary to determine the utility of JAK/Syk inhibitors in the treatment of autoimmune skin disease. In addition, it is often difficult to measure improvement of individual skin lesions when treated with topical medicines, when clearance may not be the same across all lesions. Therefore, we used the results of this study to evaluate an approach to assessing individual lesions. This method, called computerized planimetry, was used to digitally trace photos of specific skin lesions and was reliable for measuring the area of a DLE lesion. Therefore, this tool has the potential to be used to measure the extent of disease activity in individual lesions treated with topical medicines in future DLE trials. Abstract : Linked Article:  Presto et al. Br J Dermatol 2018; 178 :1308–1314